2022
DOI: 10.21037/apm-22-1026
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine 20 mg combined with sufentanil 2 μg/kg exerts a better postoperative analgesia effect in patients undergoing a second cesarean section: a randomised trial

Abstract: Background: Pain management following cesarean section remains a challenge, with many puerpera suffering from severe acute postoperative pain. And for a second cesarean section the degree of uterine contraction pain is more severe and frequent than that of a primipara. This study investigated the effect of different doses of nalbuphine combined with sufentanil for postoperative analgesia in patients undergoing a second cesarean section. Methods:We prospectively recruited 168 women with a scarred uterus undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As reported, respiratory depression and bradycardia could be elicited by SUF, 38 while NAL had ceiling effect for not causing a respiratory depression 29 . A previous study demonstrated that as compared with SUF alone for postoperative analgesia in patients undergoing a second cesarean section, NAL combined with SUF exerted decreased incidence of respiratory depression with less dizziness and sleepiness 39 . Moreover, Wang et al found the rates of postoperative respiratory depression and bradycardia were significantly lower for the patients received NAL + SUF than those received SUF alone 40 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As reported, respiratory depression and bradycardia could be elicited by SUF, 38 while NAL had ceiling effect for not causing a respiratory depression 29 . A previous study demonstrated that as compared with SUF alone for postoperative analgesia in patients undergoing a second cesarean section, NAL combined with SUF exerted decreased incidence of respiratory depression with less dizziness and sleepiness 39 . Moreover, Wang et al found the rates of postoperative respiratory depression and bradycardia were significantly lower for the patients received NAL + SUF than those received SUF alone 40 .…”
Section: Discussionmentioning
confidence: 76%
“…29 A previous study demonstrated that as compared with SUF alone for postoperative analgesia in patients undergoing a second cesarean section, NAL combined with SUF exerted decreased incidence of respiratory depression with less dizziness and sleepiness. 39 Moreover, Wang et al found the rates of postoperative respiratory depression and bradycardia were significantly lower for the patients received NAL + SUF than those received SUF alone. 40 In present study, fewer adverse reactions in the Group II when compared with Group I, including postpartum respiratory depression, nausea/vomiting, urinary retention, and bradycardia/hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, remifentanil, an ultra-short-acting opioid, was used for maintenance anesthesia in this study, which may exist acute opioid tolerance or hypersensitivity after surgery [29] . This may be related to the up-regulation of the cAMP pathway and the activation of the NMDA receptor, which leads to central sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dexmedetomidine combined with opioids can significantly increase the analgesic effect and play a synergistic role. In addition, remifentanil, an ultrashort-acting opioid, was used for maintenance anesthesia in this study, which may cause acute opioid tolerance or hypersensitivity after surgery (27). This may The serum levels of ACTH, IL-6, and COR in children 1 day before surgery and 1 and 2 days after operation of the four groups as determined by the ELISA methods.…”
Section: Group 1 H 2 H 4 H 12 H 24 H 48 Hmentioning
confidence: 99%